Red Soil in Northern Sri Lanka is a Natural Magnetic Ceramic - Ahilan, K.; Ketheeswaren, S.; Bennett, M.; Aronson, M.C. (World Scientific Publishing Co. Pte. Ltd., 2006)
The scope of the studies is to explore electric and magnetic properties of Fe3+ ion rich red soils in Northern Sri Lanka. Six samples were collected at different locations in Northern Jaffna peninsula, Sri Lanka for this investigation. Reported studies involve current-voltage (IV) measurements at room temperature of fresh, moisture-freed (115°C at 48 hrs), and annealed (1000°C at half an hour) conditions. At the fresh condition moisture dominates and is responsible for much of its transport properties. However, we are reporting that Fe3+ ions influence its transport properties in the moisture-freed and annealed conditions. Even though moisture-freed and annealed samples follow sub-linear IV behaviour the quantitative values suggest that the samples are very close to insulators (or semiconductor-insulator boundary). High field magnetization measurements up to 7 T at 1.8 K show all the samples reach the saturation moments around at 2.5 T, where the behaviour is very much similar to ferromagnetic materials. The highest saturated moment reported is ~10-3 μB/Fe3+ and the lowest is 6.5×10-4 μB/Fe3+. Also, we are presenting the inverse magnetic susceptibility-temperature (1/χ(T)) measurements from room temperature (300 K) down to 1.8 K, which suggest that critical temperature Tc is around 30 K. Perhaps, the red-soil be a natural magnetic ceramic.